In silico phylogenetic, physicochemical, and structural characteristics of phytase enzyme from ten Aspergillus species - Ridwan Putra Firmansyah; Shobiroh Nuur Alimah; I Made Artika; Popi Asri Kurniatin (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2024)
Phytic acid is a chemical compound consisting of inositol and phosphoric acid and is an antinutrient compound found in monogastric poultry feed ingredients made from cereal crops. Phytase hydrolyzes phosphoester bonds in phytic acid, releasing inorganic phosphate and phosphate esters. Aspergillus is a genus of molds that produce phytase and has been widely used in phytase production because they are easy to culture. This study aims to compare the structures, physicochemical characteristics, and phylogenetic relationships of phytases from several species of Aspergillus in silico as an initial screening step in obtaining the most suitable phytase to be used in poultry feed. Phylogenetic trees were constructed using MEGA 11 and physicochemical characteristics were analyzed using ProtParam. Protein structures were modeled with AlphaFold. The phytase structures were then docked with phytic acid using the YASARA Structure. The results showed that phytase 1QFX from Aspergillus niger, P34755 from A. awamori, and D5HQ11 from A. ficuum have very high similarity in terms of phylogenetics, sequences, physicochemical characteristics, and protein structures. The docking results from the three phytase structures showed that phytase 1QFX has the most negative ΔG value and the lowest Kd, which indicated the highest affinity to the phytic acid substrate. This research concludes that among the three phytase structures that have been compared and docked with phytic acid, phytase 1QFX from A. niger is the most suitable to be applied to poultry feed.